Effect of subsolvus and supersolvus solution treatments on the high temperature creep behavior of TC21 titanium alloy with basket-weave microstructure - L.M. Chen; L.R. Xiao; Y.F. Xu; L.R. Zeng; X.J. Zhao; S. Zhang; C. Liu; Z. Fu (Journal of Materials Research and Technology)
In this study, the TC21 (Ti–6Al–2Sn–2Zr–3Mo–1Cr–2Nb-0.1Si) alloy with basket-weave microstructure was subjected to subsolvus + aging (910 °C + 550 °C) and supersolvus + aging (1010 °C + 550 °C) treatments to optimize the performance of aircraft engine casings and other high-temperature resistant components at service temperatures of 400–600 °C. The relationship between the microstructure and high-temperature creep behavior was investigated. The creep behavior was analyzed using the Arrhenius equation to derive a constitutive model, and the creep mechanisms were determined in conjunction with the microstructural observations. Compared to the as-received and supersolvus + aging samples, subsolvus + aging samples exhibited 2.1 times longer creep life at 600 °C/500 MPa and the lowest steady-state creep rate (1.158 × 10−4/s at 600 °C/500 MPa), primarily attributed to a complete basket-weave structure with thickened lamellar primary α phase (0.8 μm) and nano-scale secondary α precipitates within refined β grains (150–200 μm). Microstructure changes didn't alter the fundamental creep mechanism. At lower temperature of 400–500 °C under 300–500 MPa, low activation energies (56.3–82.9 kJ/mol) indicated oxygen diffusion-dominated creep, while higher temperatures (500–600 °C) yielded elevated activation energies (301–411.9 kJ/mol) due to α/β-Ti self-diffusion. Stress exponent n values increased, ranging 1.5–1.8 (400 °C), 2.2–2.7 (500 °C) and 5.1–6.4 (600 °C), confirming a transition from dislocation slip-diffusion coupling to dislocation climb-dynamic recrystallization dominance.